Bauxite residue as an iron‐based catalyst for catalytic cracking of naphthalene, a model compound for gasification tar. (2nd October 2020) - Madadkhani, Shiva; Burhenne, Luisa; Bi, Xiaotao; Ellis, Naoko; Grace, John R.; Lewis, Tyler
Abstract: An iron‐based catalyst from bauxite residue (aka BR and red mud) was developed for removing biomass gasification tar. Its performance was investigated with naphthalene as the model tar compound. This was achieved by measuring the catalytic naphthalene conversion at five space velocities and at four temperatures in the 500°C to 800°C range, both in a N2 environment and in 13 vol% H2 with the balance N2 for 14 hours to determine the long‐term performance. The physical and chemical characteristics of the catalyst were studied prior to and after exposure to naphthalene to track the evolution of the catalyst as a result of the chemical reaction. In addition, the effects of calcination temperature and reduction with H2 on the surface characteristics were investigated. The bauxite residue catalyst was shown to be significantly active for naphthalene cracking, with its activity comparable to that of an industrial Ni catalyst. Activity measurements over 14 hours of testing showed that the catalyst activity decreased from 98% to 65% naphthalene conversion with time as a result of catalyst deactivation when tested in a N2 reaction environment. In the presence of 13 vol% H2 ; however, the activity maintained >95% conversion for the entire duration of the experiment.